PENGARUH BRAND IMAGE DAN TRUST IN A BRAND TERHADAP BRAND LOYALTY PADA PRODUK SEPATU OLAHRAGA NIKE DI KOTA PONTIANAK - B11109128, Muhammad Ifdal (Jurnal Manajemen Update, 2014)
Research is to analyze are variable brand image and variable trust in a brand having influence against brand loyalty to Nike sports shoes products. This research designed as research associative / causal. The population of this research is respondents consumers Nike sports shoes inÂ  Pontianak City. The technique of the withdrawal of samples used is a technique purposive of sampling by the number of samples as many as 100 people of respondents in the City of Pontianak. Technique analysis used is linear regression analysis of multiple with using program spss version 20.0. The results of data processing show that brand image and trust in a brand separatedly (partial) and together (simultaneous) influential positive and significantly to brand loyalty to Nike sports shoes products in Pontianak City, with a significance value amounting 0,000 and value R2 amounting to 33.2 %, while the rest of 66,8 % is the other factors that aren t pursuing in this research. Keywords: Brand Image, Trust in a Brand and Brand Loyalty